Epidemiology of time loss groin injuries in a men's professional football league: a 2-year prospective study of 17 clubs and 606 players. Issue 5 (30th June 2017) - Mosler, Andrea B; Weir, Adam; Eirale, Cristiano; Farooq, Abdulaziz; Thorborg, Kristian; Whiteley, Rod J; Hӧlmich, Per; Crossley, Kay M
Abstract : Background/Aim: Groin injury epidemiology has not previously been examined in an entire professional football league. We recorded and characterised time loss groin injuries sustained in the Qatar Stars League. Methods: Male players were observed prospectively from July 2013 to June 2015. Time loss injuries, individual training and match play exposure were recorded by club doctors using standardised surveillance methods. Groin injury incidence per 1000 playing hours was calculated, and descriptive statistics used to determine the prevalence and characteristics of groin injuries. The Doha agreement classification system was used to categorise all groin injuries. Results: 606 footballers from 17 clubs were included, with 206/1145 (18%) time loss groin injuries sustained by 150 players, at an incidence of 1.0/1000 hours (95% CI 0.9 to 1.1). At a club level, 21% (IQR 10%–28%) of players experienced groin injuries each season and 6.6 (IQR 2.9–9.1) injuries were sustained per club per season. Of the 206 injuries, 16% were minimal (1–3 days), 25% mild (4–7 days), 41% moderate (8–28 days) and 18% severe (>28 days), with a median absence of 10 days/injury (IQR 5–22 days). The median days lost due to groin injury per club was 85 days per season (IQR 35–215 days). Adductor-related groin pain was the most common entity (68%) followed by iliopsoas (12%) and pubic-related (9%) groin pain. Conclusion: Groin pain caused time loss for one in five players each season. Adductor-related groin pain comprised 2/3 of all groin injuries. Improving treatment outcomes and preventing adductor-related groin pain has the potential to improve player availability in professional football.